Cholesterol esterase inhibitory activity of bioactives from leaves of Mangifera indica L - Gururaja G. M.; Deepak Mundkinajeddu; Shekhar M. Dethe; Gopala K. Sangli; Abhilash K.; Amit Agarwal (Pharmacognosy Research, 2015)
Background: In the earlier studies, methanolic extract of Mangifera indica L leaf was exhibited hypocholesterol activity. However, the bioactive compounds responsible for the same are not reported so far. Objectives: To isolate the bioactive compounds with hypocholesterol activity from the leaf extract using cholesterol esterase inhibition assay which can be used for the standardization of extract. Materials and Methods: The leaf methanolic extract of M. indica (Sindoora variety) was partitioned with ethyl acetate and chromatographed on silica gel to yield twelve fractions and the activity was monitored by using cholesterol esterase inhibition assay. Active fractions were re-chromatographed to yield individual compounds. Results and Discussion: A major compound mangiferin present in the extract was screened along with other varieties of mango leaves for cholesterol esterase inhibition assay. However, the result indicates that compounds other than mangiferin may be active in the extract. In vitro pancreatic cholesterol esterase inhibition assay was used for bioactivity guided fractionation (BAGF) to yield bioactive compound for standardization of extract. Bioactivity guided fractionation afford the active fraction containing 3β-taraxerol with an IC50 value of 0.86μg/ml. Conclusion: This study demonstrates that M.indica methanol extract of leaf have significant hypocholesterol activity which is standardized with 3β-taraxerol, a standardized extract for hypocholesterol activity resulted in development of dietary supplement from leaves of Mangifera indica.
Keywords: 3 β-taraxerol.; Bioactivity; Hypocholesterol; Mangifera indica